Polymerization of aniline hydrochloride in reverse of microemulsion by batch and semicontinuous process using ionic and nonionic surfactants - G. Pier Villegas; A.G. Alvarado Mendoza; L.G. Guerrero Ramírez; L.C. Rosales-Rivera; J. Aguilar; F.J. Moscoso Sánchez (Designed Monomers and Polymers, 2022)
The polymerization of aniline hydrochloride by inverse microemulsion in a batch process and the semicontinuous process was studied as a function of the surfactant ionic and nonionic. Polymerizations were carried out at 60°C for 4 h with a yield polymer of circa 67 and 27% wt. for ionic and nonionic surfactants. The conductivity of synthesized polyaniline by the semicontinuous process is higher up to three orders of magnitude than that of the batch process for both surfactants. The calculating degree of oxidation by UV-Vis showed the relative intensities of the quinoid to benzenoid unit around one. The morphology was determined by Scanning Electron Microscopy (SEM) and observed that the formation of the different morphologies is due to the self-assembly behavior of surfactant. The diameter z-average particle size (Dz) was studied by Transmission Electron Microscopy (TEM), which determined that the diameter particle in a semicontinuous state is larger than the one produced in a batch; this is due to the control of monomer addition in the system. These findings suggest that the polymerization process and the type of surfactant influence the properties of polyaniline.